Drug hypersensitivity in children: report from the pediatric task force of the EAACI Drug Allergy Interest Group. Issue 2 (17th November 2015) - Gomes, E. R.; Brockow, K.; Kuyucu, S.; Saretta, F.; Mori, F.; Blanca‐Lopez, N.; Ott, H.; Atanaskovic‐Markovic, M.; Kidon, M.; Caubet, J.‐C.; Terreehorst, I.; ,
Abstract: When questioned, about 10% of the parents report suspected hypersensitivity to at least one drug in their children. However, only a few of these reactions can be confirmed as allergic after a diagnostic workup. There is still a lack of knowledge on drug hypersensitivity (DH) epidemiology, clinical spectrum, and appropriate diagnostic methods particularly in children. Meanwhile, the tools used for DH management in adults are applied also for children. Whereas this appears generally acceptable, some aspects of DH and management differ with age. Most reactions in children are still attributed to betalactams. Some manifestations, such as nonsteroidal anti‐inflammatory drug‐associated angioedema and serum sickness‐like reactions, are more frequent among young patients as compared to adults. Risk factors such as viral infections are particularly frequent in children, making the diagnosis challenging. The practicability and validity of skin test and other diagnostic procedures need further assessment in children. This study presents an up‐to‐date review on epidemiology, clinical spectrum, diagnostic tools, and current management of DH in children. A new general algorithm for the study of these reactions in children is proposed. Data are presented focusing on reported differences between pediatric and adult patients, also identifying unmet needs to be addressed in further research.